Deformation of Fe2Ni prepared by metal powder injection molding - MU Jianghan; LIU Shumei; LI Dajie; YANG Hangzhou; ZHOU Haitao (Fenmo yejin jishu)
In the process of the metal powder injection molding Fe2Ni, the deformation problem was present due to the uneven distribution of metal powders caused by the poor bonding of binder and shear heat generation. The flow and coupling properties of feedstock in three powder loads were compared by melt index experiment in this paper. The gate area, mold temperature, and injection temperature were optimized by Taguchi method, range analysis, and variance analysis, and the influence of process parameter interaction on the shear stress was studied. The results show that the optimum process parameters are the powder loading capacity (volume fraction) 62.5%, the gate surface 23.984 cm2, the mold temperature 69.854 ℃, and the injection temperature 194.323 ℃. Through the verification analysis of Moldex 3D software, the shear stress of the products is the minimum, the powder uniformity is the highest, and the deformation of the final products is improved.